193k views
2 votes
Simplify 13 over the quantity of negative 3 plus 2i.

−3 + 2i
−3 − 2i
2i + 3
−2i + 3

User Thisisdog
by
6.5k points

1 Answer

4 votes


(13)/((-3+2i))

To simplify we need to rationalize it. which can be done by multiplying composite of denominator. That is multiply by -3-2i


=(13)/((-3+2i))*((-3-2i))/((-3-2i))

Now multiply numerator with numerator and denominator with denominator


=((-39-26i))/((-3)^2-(-2i)^2)


=((-39-26i))/(9-(4i^2))


=((-39-26i))/(9-(4(-1)))


=((-39-26i))/(9-(-4))


=((-39-26i))/(9+4)


=((-39-26i))/(13)


=-3-2i

Hence final answer is
=-3-2i

User Jeach
by
5.5k points